Performance Analysis of the SAE AS4074.2 High Speed Ring Bus - Minnich, David (University of Virginia, Department of Computer Science, 1988)
In recent years, a new generation of high speed network protocols has begun to emerge. These networks, typically operating in the 100 Mbps range, include the ANSI Fiber Distributed Data Interface (FDDI) and the SAE AS40742 High Speed Ring Bus (HSRB). The Computer Networks Laboratory at the University of Virginia, seeing the need for an in-depth understanding of the operation of these protocols, has been conducting simulations and performance analyses of these networks. A general token-ring simulation system has been developed which allows analysis and comparison of these various protocols. The usefulness of this system is three-fold: 1) it allows performance analysis of network protocols for which no hardware currently exists, 2) the results of this analysis may be used to suggest protocol improvements to the design committee, and 3) network implementors may use the system to tune the protocols and determine optimum configurations. The thesis includes a discussion of the simulation system in general, the SAE HSRB protocol in particular, and the results of the performance analysis. Note: Abstract extracted from PDF file via OCR
Original submission date: 2013-10-11T17:21:32Z